Pengaruh Penambahan Abu Limbah Kulit Kakao Terhadap Koefisien Permeabilitas Tanah dan Piping - Voniyanti Arungtasik; Irwan Lie Keng Wong; Benyamin Tanan (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
This study was carried out to determine the effect of cocoa shell waste ash on soil permeability and piping. This is because clay soil has a poor carrying capacity where the condition of the soil does not allow for road construction to be built on it. Therefore, it is necessary to make efforts to improve the condition of the soil, one of the most common ways is to stabilize the soil. Soil sampling was carried out in Lambanan Village, Mamasa District, Mamasa Regency, and added materials using cocoa shell waste ash located in Lambara Harapan, Burau District, East Luwu Regency with the percentage of added material at the soil permeability coefficient, namely 0%, 5%, 10%, 15% and in piping used percentages of 0% and 15%. The achievement structure in this study is to use a series of studies on the physical properties of the soil so that it can produce soil permeability coefficients and piping. Testing of soil physical properties was carried out at the Uki Paulus Soil Mechanics Laboratory in Makassar. The results of this study showed that the soil meets the characteristics as loamy soil. The effect of adding cocoa shell waste ash to the soil is that there is a decrease in permeability where the higher the percentage of cocoa shell waste ash, the smaller the permeability value to the addition of 15%, while in piping there is an increase in the addition of 15%.